Fear dot com - Coyle, Josephine; Pike, Nicholas (Warner Home Video, 2003)
A mad genius has created a live-cam website that determines a person's deepest fear and then 48 hours later that fear becomes a brutal reality. An investigating detective and a city health inspector know the danger of logging into the site, but both are determined to solve the mystery.